ORIENTALIUM ECCLESIARUM: SECOND VATICAN COUNCIL DECREE ON THE EASTERN CATHOLIC CHURCHES – A HISTORICAL SURVEY - Thonippara, Francis (Asian Horizons, 2014)
The main focus of the article is the historical background of the evolution of the Decree on the Eastern Catholic Churches of the Second Vatican Council. Although criticisms have been raised against the Decree, it is a landmark in the relationship between the Eastern Churches, both Catholic and non-Catholic, and the Roman Catholic Church. This Decree reminds the Roman Catholic Church of the communion nature of the Church and the equal right, dignity and obligation of the individual churches in the communion. This Decree exhorts the Eastern Catholic Churches to be aware of their individuality and to be faithful their identity. This Decree is a great boost to those who are engaged in ecumenism as it makes special efforts to underline the richness of the Eastern Churches. Although many questioned the need for a separate Decree on the Eastern Catholic Churches, the determined efforts of Popes John XXIII and Paul VI and cardinals Augustine Bea and Jan Willebrands made this Decree a reality. The efforts of delatinisation which were initiated and implemented in the light of this Decree, bear ample fruits in the Eastern Catholic Churches.